Evolutionary responses of Drosophila melanogaster to selection at different larval densities: changes in genetic variation, specialization and phenotypic plasticity - Perez, A; Garcia, C (Journal of evolutionary biology, 2002)
We studied the evolutionary response to novel environments by applying artificial selection for total progeny biomass in populations of Drosophila melanogaster maintained at three different larval population densities. We found the relative amount of genetic variability for characters related with biomass to be lower and the correlation between them more negative at the intermediate density, and that selection resulted in changes in phenotypic plasticity and in patterns of resource allocation between traits. We found some evidence for tradeoffs between densities, which suggests that populations living at heterogeneous densities might be subject to disruptive selection. Our results show that adaptation to new environments may be a complex process, involving not only changes in trait means, but also in correlations between traits and between environments.